Estimates of the global reduction in liver disease‐related mortality with increased coffee consumption: an analysis of the Global Burden of Disease Dataset. Issue 7 (14th August 2020) - Gow, Paul; Spelman, Tim; Gardner, Sarah; Hellard, Margaret; Howell, Jessica
Summary: Background: Epidemiological data suggest that coffee has a dose‐dependent protective effect on liver‐related mortality. Aim: To estimate the potential impact of increased per capita coffee consumption on global liver‐related mortality. Methods: Using the Global Burden of Disease 2016 dataset (adults > 15 years), we modelled the impact of increased per capita coffee consumption on liver‐related mortality in 2016 for 194 countries using published risk ratios for >2 cups coffee/ day (RR 0.54, 95% CI 0.42‐0.69) and ≥4 cups/ day (RR 0.29, 95% CI 0.17‐0.50), adjusted for confounders and tested model assumptions using sensitivity analyses. Results: Worldwide, there were an estimated 1, 240, 201 (95% CI 118 4300‐1 354 410) adult liver‐related deaths in 2016. Median global liver mortality rate in 2016 was 15 deaths/ 100 000 population/ year (all ages, both genders; IQR 11‐21 deaths per 100 000). If all countries with per capita coffee intake ≤2 cups/ day increased to >2 cups/ day, the predicted total number of liver‐related deaths would have been 630 947 in 2016 (95% CI 629 693‐631 861) with 452 861 (95% CI 451 948‐454 116) deaths averted (PPR 7.8 liver‐related deaths/ 100 000/ year). If per capita consumption was ≥ 4 cups/ day, the predicted number of liver‐related deaths in 2016 would have been 360 523 (95% CI 359 825‐361 992) with 723 287 (95% CI 721 817‐723 984) deaths averted (PPR 12.1 liver‐related deaths/100 000/year). Conclusion: Increasing per capita coffee consumption to > 2 cups per day on a population level has the potential to avert hundreds of thousands of liver‐related deaths annually if the impact of coffee on liver‐related mortality is confirmed in clinical trials.